REDESAIN STAN PEDAGANG SUVENIR DILINGKUNGAN MUSEUM SANGIRAN SRAGEN DENGAN PENDEKATAN ERGOKULTURAL - Haryanto, Eko sri; Utomo, Tri Prasetyo (Acintya, 2019)
The souvenir product booth is an important tool that is used to support the smooth running of business activities in public space for traders. The souvenir product booth is used by sellers to display their merchandise to attract visitors to come and do buying and selling activities. This applied research aims to determine the condition of the souvenir merchant product booth at the Sangiran Museum, then analyze and synthesize, then do a new booth redesign that is in accordance to the demands of function, ergonomics, culture and image of Sangiran Museum tourism object. The design of the new booth was made so that it could function properly to support the display of the typical Sangiran products sold. In the end, it was hoped that there would be additional transactions so as to increase the sales turnover of souvenir merchants in Sangiran Museum area. The design is made based on the rules of function, safe and comfortable ergonomically, and has a distinctive character according to the tourist destinations in Sangiran Museum.The object of applied design research is the product stand for souvenir merchants in SangiranMuseu. The method used is descriptive with a qualitative approach supported by quantitative dataor can be called a multiple research strategy. Quantitative data here means using numerical data which is the result of measurement in the field, then compared to the references, resource persons and analyzed based on the researcher interpretation. The design activities begin with product discovery stage to obtain innovative creations in the product design process.The results of applied art / design research are in the form of designs and booths that are in accordance to the rules; functions, ergonomics, beauty and image of Sangiran Museum. The results of the creation of art / design are also expected to provide material for the Interior Design and Furniture Design Courses in Interior Design Study Program, ISI Surakarta.  Keywords  : booth redesign, ergonomics, culture, Sangiran Museum